CALL FOR APPLICATIONS: IMPROVE SCHOLARS WRITING SKILLS BY USING ONLINE COLABORATIVE WRITING - Prayoga, Adhitya (STKIP CITRA BAKTI, 2023)
Computer-assisted language learning (CALL) is a guidelines approach that utilizes innovation to improve dialect capability, especially in composing. Scholars have access to different programs or websites that can help them in moving forward with their composing aptitudes. In this specific consideration, the center was on examining whether the utilization of Google Docs for online collaborative composing seems upgrade learners' composing capacities. The members of the study were scholars selected within the English Literature Study Program (Bachelor Degree) at Mahasaraswati University. A add up to of 60 scholars were chosen as tests, with 30 scholars doled out to the Treatment group and another 30 to the Test group. Amid a 4-week composing course, the tests locked in bunch composting hones utilizing Google Docs. Information collection included regulating pre-tests, post-tests, and surveys, which were at that point analyzed employing a blended strategies approach. The discoveries show that the Free Tests t-Test (t-count) yielded a score of 6.531, whereas the t-table esteem was 2.007, and the p-value was 0.000. These come about suggest that utilizing Google Docs as a stage for collaborative composing exercises encompasses a critical effect on scholars' composing aptitudes. The truth that the t-count scores surpass the t-table values and the p-values are below 0.05 demonstrates the nearness of a normal contrast between the scores of the Treatment class scholars and the Test class scholars